Looking at The Violation of The Semarang Mayor Election Process With A Perspective of Conflict in 2020 - Masrohatun, Masrohatun; Elizabeth, Misbah Zulfa; Maria Ulfa, Novi; Ali Aziz, Rifki; Darsyah, Moh Yamin (JPW (Jurnal Politik Walisongo), 2024)
Violations during the Mayoral Election process are certainly not new. The dynamics were changing during the election process. These violations are certainly evaluation material for the organizing body in the effort to resolve the problem. However, this problem can spark conflict between partisans, organizers, and candidates. Therefore, this article aims to see what forms of violations were during the Semarang of Mayoral Election process, to see violations through the lens of conflict. With a qualitative research method, a case study approach with conflict theory, this study presents information that violations found include violations at the stages of the election process and violations at non-stages. These violations are more directed at administrative violations in the data collection of permanent election candidates, Ad-hoc committee candidates, violations in the implementation of the campaign, ASN neutrality, vote recounts, and errors in filling out form D. These violations are said to be conflicts because one party has different goals with another. The violations that occur were included in the type of surface conflict but do not rule out the possibility of becoming alternative conflicts and open conflicts in the future because all citizens did not obtain political education so they did not understand how politics works properly.